A Vietnamese-American cross-cultural study of giving comments on contestants’ performance by judges in Vietnam and American Idol - Trần, Thị Hoàng Ngân (University of Languages and International Studies, 2017)
This thesis focuses on cross-cultural similarities and differences in giving comments on contestants’ performance by judges in Vietnam Idol and American Idol. Politeness strategies realized for giving comments are analyzed with data taken from the video cl (...)